29.0k views
17 votes
O Watch help video

-
=
Given that f(x) = x2 - 6x + 8 and g(x) = X – 2, find (fºg)(x) and express
the result in standard form.

User SonicBison
by
6.7k points

1 Answer

5 votes

Answer:
x^(2) -7x+10

Step-by-step explanation:

Get the result ⇒
f(x)-g(x)=(x^(2) -6x+8)-(x-2)

Remove the parentheses ⇒
x^(2) -6x+8-x+2

Reorder and gather like terms ⇒
x^(2) +(-6x-x)(8+2)

Collect the coefficients for the like terms ⇒
x^(2) +(-6-1)*x+(8+2)

Calculate the sum or difference ⇒
x^(2) -7x+(8+2)

Calculate the sum or difference ⇒
x^(2) -7x+10

Convert to required form ⇒
x^(2) -7x+10

Answer ⇒
x^(2) -7x+10

User Teesha
by
5.9k points